2022
DOI: 10.1002/jev2.12276
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from the choroid plexus trigger the differentiation of neural stem cells

Abstract: The choroid plexus secrets cerebrospinal fluid (CSF) composed of electrolytes, cytokines, growth factors, metabolites and extracellular vesicles (EVs) that flow through the interconnected brain ventricles. On their course, CSF components can act as signals that affect, for example, neural stem cells (NSCs) residing in niches of the ventricular wall. We studied EV‐born CSF signals in an in vitro culture system. We purified EVs from the secretome of a choroid plexus cell line (Z310 cells), and from primary choro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…The results of this research are the same as research conducted by Ditte Ayu Suntara et al, (2022). Based on the results of the Chi-Square analysis, it is known that the p value is 0.005<0.05 (which is shown in the Asymp.Sig column) in the computer output, so Ho is rejected and Ha is accepted, meaning that there is a relationship between physical activity and uric acid (gout) levels in elderly.…”
Section: Resultsmentioning
confidence: 62%
“…The results of this research are the same as research conducted by Ditte Ayu Suntara et al, (2022). Based on the results of the Chi-Square analysis, it is known that the p value is 0.005<0.05 (which is shown in the Asymp.Sig column) in the computer output, so Ho is rejected and Ha is accepted, meaning that there is a relationship between physical activity and uric acid (gout) levels in elderly.…”
Section: Resultsmentioning
confidence: 62%
“…In one trial, 24 volunteers showed good tolerance to nebulized mesenchymal stromal cells-derived EVs, with no serious adverse events reported up to 7 days post-nebulization [ 86 ]. Other studies confirm EVs’ role in enhancing neural differentiation [ 87 , 88 ], and the regulation of endogenous NSCs for neurogenesis post-SCI is also validated [ 89 ]. Further research is required to translate these findings into practical CNS injury treatment methods.…”
Section: Discussionmentioning
confidence: 81%
“…Even with the possibility of cytosolic proteins released from the broken ventricular area or dying neuroepithelial cells, the CSF proteome of mouse embryos could be affected by the proliferative condition of the mouse embryonic neuroepithelium and the secretory status of the choroid plexus. The secretion of extracellular vesicles and secretory proteins from both neuroepithelium and the choroid plexus could be regulated from signaling pathways downstream of the cilium [ 74 , 75 , 76 ]. We figured that signaling through the primary cilia could be regulated from CSF factors.…”
Section: Resultsmentioning
confidence: 99%